(untitled) (Clinics, 2021)
OBJECTIVES: This study aimed to determine the effects of age, race/ethnicity, body mass index, and contraception on human chorionic gonadotropin (hCG) regression following the evacuation of a molar pregnancy. METHODS: This was a retrospective cohort study of 277 patients with molar pregnancies between January 1, 1994 and December 31, 2015. The rate of hCG regression was estimated using mixed-effects linear regression models on daily log-transformed serum hCG levels after evacuation. RESULTS: There were no differences in hCG half-lives among age (p=0.13) or race/ethnicity (p=0.16) groups. Women with obesity and hormonal contraceptive use demonstrated faster hCG regression than their counterparts (3.2 versus. 3.7 days, p=0.02 and 3.4 versus. 4.0 days, p=0.002, respectively). CONCLUSION: Age and race/ethnicity were not associated with hCG regression rates. Hormonal contraceptive use and obesity were associated with shorter hCG half-lives, but with unlikely clinical significance. It is important to understand whether the clinical characteristics of patients may influence the hCG regression curve, as it has been proposed as a way to predict the risk of gestational trophoblastic neoplasia.